Penegakan Hukum terhadap Prajurit TNI yang Melakukan Pelanggaran Lalu Lintas Berkendara tanpa Surat Izin Mengemudi (SIM) di Tinjau dari UU No 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan (Pusat Riset dan Inovasi Nasional, 2026)
The Indonesian National Army as a member of the Indonesian National Guard is at the forefront of Indonesia in the eyes of the public as an example and role model in discipline, ethics, and compliance with the law. However, in the reality of daily life, there are still TNI soldiers who commit traffic violations, such as driving a vehicle without having a Driver's License (SIM). This research includes empirical juridical research, or called field research, which examines the applicable legal provisions and compares them with the reality that occurs in society. The research method used was in the form of interviews with five relevant sources, then the data was analyzed descriptive-qualitatively to provide a comprehensive understanding. The results of the study showed that (1) law enforcement against TNI soldiers who committed traffic violations without a driver's license was checked according to the procedure of the rapid inspection event; no long inspection minutes are required, it is enough to use the minutes of traffic violations and road transportation or tickets from the military police; (2) Sanctions applied for minor traffic violations in the form of administrative disciplinary sanctions, including criminal prosecution of fines paid to military authorities and deposited into the state treasury. This reflects the balance between legal compliance and internal discipline of the TNI, as well as efforts to develop soldiers so that they remain an example for the community.